Analysis Of The Influence Of Service Quality And Food Quality On The Behavioral Intentions Of Burger King Online Food Delivery Customers In Bandung City With Customer Satisfaction As An Intervening Variable - Alfrida Wira Kusuma Astuti; Mochamad Yudha Febrianta (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
With the rapid technological advancement, individual demands have evolved, prompting Indonesians to engage in online buying and selling. This trend extends beyond physical goods, as there is an increasing preference for utilizing Online Food Delivery (OFD) services, simplifying food orders. This study focuses on the challenges faced by Burger King's online food delivery customers, stemming from service and food quality issues, ultimately impacting satisfaction and behavioral intentions. Therefore, this study aims to determinane effect of service quality and food quality on customer satisfaction and customer behavioral intentions of Online Food Delivery Burger King customers in the city of Bandung with customer satisfaction as an intervening variable. This study uses the independent variable, namely service quality which includes perceived control, convenience, customer service, fulfillment and food quality, the intervening variable is customer satisfaction and the selected dependent variable is behavioral intention. Employing a quantitative approach, the study's population comprises Burger King's online food delivery customers, with a sample size of 400 in Bandung. Data collection involves distributing online questionnaires via Google Forms, targeting users residing in Bandung who utilize the Burger King app. The research methodology encompasses descriptive quantitative analysis through SEM-PLS examination, using SmartPLS 3.0 software. The findings demonstrate that perceived control, convenience, customer service, fulfillment, and food quality all positively and significantly impact customer satisfaction, which subsequently positively influences behavioral intentions. This study proposes recommendations for companies to enhance service quality, particularly regarding customer service accessibility, and to prioritize food quality by offering fresh products.